Angiospermic flora of Gafargaon upazila of Mymensingh district focusing on medicinally important species (Bangladesh Journal of Plant Taxonomy, 2019)
Gafargaon upazila has been floristically explored to identify and assess the angiospermic flora that resulted in occurrence of 203 taxa under 174 genera and 75 families. Magnoliopsida is represented by 167 taxa under 140 genera and 62 families, while Liliopsida is constituted by 36 taxa belonging to 34 genera and 13 families. Vegetation analysis shows that herbs are represented by 106 taxa, shrubs 35, trees 54, and climbers by 8 species. In Magnoliopsida, Solanaceae is the largest family possessing 10 species, whereas in Liliopsida, Poaceae is the largest family with 12 species. The study has identified 45 medicinal plants which are used for treatment of over 40 diseases including diabetes, ulcer, diarrhoea, dysentery, fever, cold and cough, menstrual problems, blood pressure and urinary disorders by the local people. Some noticeable medicinal plants used in primary healthcare are Abroma augusta (L.) L.f., Coccinia grandis (L.) Voigt., Commelina benghalensis L., Cynodon dactylon (L.) Pers., Holarrhena antidysenterica Flem., Glycosmis pentaphylla (Retz.) A. DC., Mikania cordata (Burm. f.) Robinson, Ocimum tenuiflorum L. and Rauvolfia serpentina (L.) Benth. A few number of species are also employed in cultural festivals in the study area. Cardamine flexuosa With., Oxystelma secamone (L.) Karst., Phaulopsis imbricata (Forssk.) Sweet, Piper sylvaticum Roxb., Stephania japonica (Thunb.) Miers and Trema orientalis L. have been found to be rare in the investigated area. In order to preserve botanical resources of Gafargaon upazila, particularly the rare, threatened and medicinal plants, conservation measures need to be undertaken through both in-situ and ex-situ methods for their sustainable use.